Dictionary of world monasticism - Olderr, Steven (McFarland & Company, Inc., Publishers, 2020)
""Despite the many volumes written about monasticism, this is the first comprehensive dictionary on the subject-not a proselytizing work but instead with a focus on history, biography and description both ancient and modern. The scope is worldwide, covering not only Christianity but all faiths that have monastic traditions including, but not limited to, Buddhism, Jainism and Hinduism."-Provided by publisher"--